Explaining environmental Kuznets curves: How pollution induces policy and new technologies - Lucas Bretschger; Sjak Smulders (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 2000)
Production often causes pollution as a by-product. Once pollution problems become too severe, regulation is introduced by political authorities which forces the economy to make a transition to cleaner production processes. We model this transition as a change in general purpose technology (GPT) and investigate how it interferes with economic growth driven by qualityimprovements. The model gives an explanation for the inverted U-shaped relationship found in empirical research for many pollutants, often referred to as the Environmental Kuznets Curve (EKC). We provide an analytical foundation for the claim that the rise and decline of pollution can be explained by policyinduced technology shifts.
Keywords: O41; Q20; 330; Environmental Kuznets curve; general purpose technology; growth; Umweltbelastung; Sozialprodukt; Umweltpolitik; Umweltschutz; Innovation; Wirtschaftswachstum; Theorie; Environmental Kuznets Curve